Pengaruh Kapasitas Organisasi terhadap Implementasi Standar Akuntansi Pemerintah Berbasis Akrual yang Dimoderasi Oleh Komitmen Organisasi - Rahmat Hidayat; Ratna Ayu Damayanti; Darmawati Darmawati (Al-Buhuts, 2022)
This study aims to determine the effect of organizational capacity and organizational commitment on the implementation of accrual-based SAP in the Majene Regency Government. Based on the research objectives which became the unit of analysis in this study, it was conducted at the organizational level. The population used in this study was 31 Regional Apparatus Organizations (OPD) in Majene Regency. The criteria used in sampling in this study were Financial Administration Officers (PPK), Treasurers, and Financial Staff at each OPD in Majene Regency, so that the population given the questionnaire was 93 employees. Sampling uses primary data collected through a questionnaire. The data were then analyzed using Structural Equation Modeling-Partial Least Squares. SEM was chosen because it is more accurate in processing data to obtain causality between variables and constructs and to determine the magnitude of the relationship between variables and constructs. The results showed that organizational capacity had a positive and significant effect on the application of accrual-based Government Accounting Standards which was moderated by organizational commitment in the Majene Regency Government.